How to Write and Publish A Scientific Paper: A Closer Look to Eastern European Economics, Business and Management Journals - Bach Mirjana Pejić (Business Systems Research, 2015)
Background: Scientific research publishing carries significant role in the development of the society. Apart from the dissemination of knowledge, there are also motives for publication of scientific research results at the level of individual researchers. Objectives: The goal of the paper is to propose simple, yet highly applicable advice when pursuing the publication of a paper in a scientific journal providing a closer look to economics, business and management journals that focus on Eastern European countries. Methods/Approach: The 4 Cs model of scientific writing and publication is presented, based on four questions: (1) How to pick a topic relevant for publication?; (2) How to select a journal for possible publication?; (3) How to structure the paper in accordance with the IMRAD format?, and (4) How to efficiently write the paper? Results: Step-by-step application of the 4C’s model is presented in the paper with an outlook to economics, business and management journals that focus on Eastern European countries. Conclusions: Publication in a scientific journal is an important venue for scientific researchers. In preparing the presentation of the scientific research results for the publication, number of issues relating content, style, composition and presentation should be taken into account.